Ultraviolet radiation and systemic lupus erythematosus. (May 2014) - Barbhaiya, M; Costenbader, KH
Exposure to ultraviolet (UV) radiation is among the environmental factors that have been proposed and studied in association with systemic lupus erythematosus (SLE). While it is known that UV radiation exposure may exacerbate pre-existing lupus, it remains unclear whether UV exposure is a risk factor for the development of SLE. Experimental studies show a significant immunomodulatory role for UV radiation, but strong epidemiologic data regarding its role in triggering SLE onset are lacking. Further studies are needed to assess the role of UV radiation in relation to development of incident SLE, yet they are challenging to design due to difficulties in accurate exposure assessment, the heterogeneous nature of SLE, and the challenge of assessing photosensitivity, a feature of SLE, which often precedes its diagnosis.